Comparison of levofloxacin versus clarithromycin efficacy in the eradication of Helicobacter pylori infection - Aliakbar Hajiaghamohammadi; Ali Bastani; Arash Miroliaee; Sonia Oveisi; Saeed Safarnezhad (Babol University of Medical Sciences, 2016)
Background: Helicobacter pylori (H.pylori) infection causes multiple upper gastrointestinal diseases but optimal therapeutic regimen which can eradicate infection in all the cases has not yet been defined. This study was designed to evaluate the efficacy of triple levofloxacin-based versus clarithromycin-based therapy. Methods: In this open-label randomized clinical trial study 120 patients who had esophagogastroduodenoscopy (EGD) with positive rapid urease test (RUT) were enrolled and divided into 2 groups. Case group was treated with levofloxacin (500 mg daily) plus amoxicillin (1 gr twice a day) plus omeprazole (20 mg daily) for 2 weeks. Control group was treated with clarithromycin (500 mg twice a day) plus omeprazole (20 mg daily) for 2 weeks. After the main course of treatment, they received maintenance treatment with omeprazole for 4 weeks. Stool antigen test was performed on them after two weeks of not having any medicine. Results: H.pylori eradication (intention to treat analysis) was successful in 75% of case group and 51.7% of control group showing a significant difference (P=0.008). H.p infection eradication (per-protocol analysis) was successful in 80.4% in case group and 57.4%% in control group showing significant difference (P=0.009). Drugs adverse effects causing discontinuation treatment were seen in 5% of  case group and 3.3% of control group which have not shown a significant difference between the two groups (P=0.648). Conclusion: Triple therapy with levofloxacin-based regimen has better efficacy than clarithromycin-based regimen and as safe as it is.